Extracellular metabolism of thyroid hormones by stimulated granulocytes. - Rao, M K (1984)
Stimulated polymorphonuclear leukocytes have been shown by this laboratory to release a reactive-oxygen species (ROS) which is detectable in the supernatant and is capable of oxidizing reduced glutathione and reacting with methionine (Sagone et al., Blood 63:96-104, 1984). This ROS is dependent on H2O2 and heme for its production and is postulated to be a stable oxidant derived from hypochlorous acid, such as a chloramine. Further, this ROS was also shown to be able to oxidize and fix iodide to protein. This latter characteristic was the theoretical basis for our present study in which the same ROS was shown to be able to carry out the iodination of 3,3,5'-triiodothyronine to thyroxine in the presence of I-. Our results provide further support that granulocytes have a role in the peripheral utilization of thyroid hormones in patients with infectious diseases or other illnesses in which granulocytes may be activated, and our results indicate that the reactions may occur extracellularly.